Financial burden of cancer in Nepal: Factors associated with annual cost and catastrophic health expenditure - Pratik Khanal; Kjell Arne Johansson; Achyut Raj Pandey; Ravi Kant Mishra; Nirmal Poudel; Sandipa Sharma; Biraj Man Karmacharya; Shiva Raj Adhikari; Krishna Kumar Aryal (PLoS ONE, 2025)
Background There is a dearth of comprehensive research on the financial burden of cancer in low-resource settings. This study aims to identify factors associated with annual cost of cancer care and catastrophic health expenditure as well as estimate the impoverishment linked with cancer treatment in Nepal. Methods This cross-sectional study was conducted in two tertiary public cancer hospitals of Nepal. Face-to-face interviews were conducted with 387 patients undergoing active treatment for lung, breast, cervical, stomach, and oesophagus cancers, recruited using a purposive-consecutive sampling strategy. A generalized linear model was used to identify factors associated with annual cost, while a multivariable logistic regression model was used for catastrophic health expenditure. Pen’s Parade diagram was plotted to estimate impoverishment linked to cancer. Results The annual average cost of cancer care was 3,687 United States Dollar (479,310 Nepalese rupees). Factors significantly associated with higher annual cancer costs included secondary and above education, treatment duration of 6–12 months and above one-year, combined treatment modalities, admission to inpatient care, and prior visits to private health facilities. Cervical cancer (compared to lung cancer) was significantly associated with lower costs. The incidence of catastrophic health expenditure was 96.9% and 83.9% at the 10% and 25% threshold of annual household expenditure, respectively. Treatment duration of 6–12 months, admission to inpatient care, and lowest to higher wealth quintiles were associated with higher odds of catastrophic health expenditure compared to treatment duration of less than six months, no admission to inpatient care, and highest wealth quintiles, respectively. Similarly, 26% of the patients experienced impoverishment associated with cancer treatment expenses. Conclusion Seeking cancer treatment posed a substantial financial risk to patients in Nepal. Most of the patients experienced catastrophic health expenditure while a quarter of the patients experienced impoverishment following cancer treatment expenses, highlighting the need for strengthened social health protection mechanisms.